Evolution of Biomaterials - Vallet-Regí, Maria (Frontiers in Materials, 2022)
There is a clear need for increasingly versatile and effective implantable biomaterials, and to train qualified personnel for research and development in the field of biomaterials design and manufacturing. In all these implantable biomaterials, science and technology are imposing new designs with combinations of new biomaterials, new coatings, new design and manufacturing technologies (biomimetic biomaterials, functional biomaterials, nanotechnology, finite element modeling, additive manufacturing, 3D printing, tissue engineering, drug delivery...) that will revolutionize the field of implants in the short term. Biomaterials are part of biomedical engineering and bring together knowledge from the world of science, engineering, biology and medicine, being a multidisciplinary field where borders have no place.